2008
DOI: 10.1007/s10761-008-0045-y
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology of Concretions, Sediments and Mechanisms Influencing the Preservation of Submerged Archaeological Artifacts

Abstract: Research conducted at deep-ocean ship wreck sites in the North Atlantic Ocean, the Mediterranean Sea and in the Gulf of Mexico have revealed that microorganisms play a significant role in both the preservation and loss of submerged artifacts. Research to be reported concentrates on the influence of microbiologically induced concretions on the survival of maritime artifacts. Rusticles, a common form of concretion, have been found to provide valuable information to archeology (Garzke et al. 1997, Proceedings of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 1 publication
(2 reference statements)
2
38
0
Order By: Relevance
“…Cullimore and Johnston (2008) consistently identified iron-related bacteria (both oxidizing [FeOB] and reducing [FeRB]), sulfate-reducing bacteria (SRB) and heterotrophic bacteria associated with rusticles from five different wreck locations. They also reported significant populations of fungi on the outer walls of rusticles.…”
Section: Rusticlesmentioning
confidence: 99%
“…Cullimore and Johnston (2008) consistently identified iron-related bacteria (both oxidizing [FeOB] and reducing [FeRB]), sulfate-reducing bacteria (SRB) and heterotrophic bacteria associated with rusticles from five different wreck locations. They also reported significant populations of fungi on the outer walls of rusticles.…”
Section: Rusticlesmentioning
confidence: 99%
“…From these parallel rusticle investigations, an estimate of rusticle growth can be made for Alcoa Puritan, where current rusticle development may be similar to that of Titanic during the mid-1970s when it had been submerged for a similar length of time (Cullimore et al, 2001;Cullimore and Johnston, 2005). refereNces…”
Section: Alcoa Puritanmentioning
confidence: 99%
“…There are many similarities between tubercles and rusticles. For instance, several investigators have demonstrated that the presence of active microorganisms within both tubercles and rusticles are mainly the iron bacteria communities . Several previous research articles on metal corrosion have mentioned that tubercle formation refers to iron corrosion products in, for instance, carbon steel and stainless steel .…”
Section: Introductionmentioning
confidence: 99%